Assessment of knowledge of primary healthcare physicians in the western region of Saudi Arabia about Hidradenitis Suppurativa - Akbar, Jumana Nabeel; Tallab, Mawaddah Abdulgader; Aljoudi, Sarah Bandar; Nukaly, Houriah Y.; Abduljabbar, Mohammed Haitham (Frontiers in Medicine, 2025)
BackgroundHidradenitis Suppurativa (HS) is a relatively common chronic inflammatory skin disorder. Early identification by primary healthcare (PHC) physicians plays a crucial role in preventing its adverse outcomes.ObjectiveTo assess the knowledge of primary healthcare physicians in the Western Region of Saudi Arabia regarding HS and identify the determinants influencing their knowledge level.MethodsA cross-sectional study was conducted among randomly selected PHC physicians working in the cities of Jeddah, Makkah, and Taif. A valid and reliable self-administered online questionnaire was used for data collection.ResultsA total of 106 PHC physicians participated in the study, with ages ranging from 26 to 48 years. The majority (79.2%) were aware of HS. The most frequently reported source of information was a diagnosed patient (64.3%). Overall, 47.2% of participants demonstrated a good level of knowledge regarding HS. Female physicians (p = 0.043), those over 35 years of age (p = 0.001), family medicine consultants (p < 0.001), physicians with more than 10 years of clinical experience (p = 0.008), and those who had seen more than five dermatological cases per day (p = 0.019) were significantly more knowledgeable. Most participants assigned the responsibility for diagnosis, treatment, and follow-up of HS cases to dermatologists, followed by surgeons or PHC physicians. About one-third (33%) had previously diagnosed a case of HS.ConclusionAlthough most PHC physicians in Western Saudi Arabia were aware of HS, less than half demonstrated a good level of knowledge, and only one-third had ever diagnosed a case. These findings highlight the need to implement targeted dermatology education programs for PHC physicians.